Conjugate Gradient Method for Estimation of Robin Coefficients. Issue 2 (May 2014) - Ma, Yan-Bo; Lin, Fu-Rong
Abstract: We consider a Robin inverse problem associated with the Laplace equation, which is a severely ill-posed and nonlinear. We formulate the problem as a boundary integral equation, and introduce a functional of the Robin coefficient as a regularisation term. A conjugate gradient method is proposed for solving the consequent regularised nonlinear least squares problem. Numerical examples are presented to illustrate the effectiveness of the proposed method.